The role of ecological factors in shaping bat cone opsin evolution. Issue 1876 (11th April 2018) - Gutierrez, Eduardo de A.; Schott, Ryan K.; Preston, Matthew W.; Loureiro, Lívia O.; Lim, Burton K.; Chang, Belinda S. W.
Abstract : Bats represent one of the largest and most striking nocturnal mammalian radiations, exhibiting many visual system specializations for performance in light-limited environments. Despite representing the greatest ecological diversity and species richness in Chiroptera, Neotropical lineages have been undersampled in molecular studies, limiting the potential for identifying signatures of selection on visual genes associated with differences in bat ecology. Here, we investigated how diverse ecological pressures mediate long-term shifts in selection upon long-wavelength ( Lws ) and short-wavelength ( Sws1 ) opsins, photosensitive cone pigments that form the basis of colour vision in most mammals, including bats. We used codon-based likelihood clade models to test whether ecological variables associated with reliance on visual information (e.g. echolocation ability and diet) or exposure to varying light environments (e.g. roosting behaviour and foraging habitat) mediated shifts in evolutionary rates in bat cone opsin genes. Using additional cone opsin sequences from newly sequenced eye transcriptomes of six Neotropical bat species, we found significant evidence for different ecological pressures influencing the evolution of the cone opsins. While Lws is evolving under significantly lower constraint in highly specialized high-duty cycle echolocating lineages, which have enhanced sonar ability to detect and track targets, variation in Sws1 constraint was significantly associated with foraging habitat, exhibiting elevated rates of evolution in species that forage among vegetation. This suggests that increased reliance on echolocation as well as the spectral environment experienced by foraging bats may differentially influence the evolution of different cone opsins. Our study demonstrates that different ecological variables may underlie contrasting evolutionary patterns in bat visual opsins, and highlights the suitability of clade models for testing ecological hypotheses of visual evolution.